Chemical composition, antioxidant and antibacterial activities and evaluation of cytotoxicity of the fractions obtained from Selaginella convoluta (Arn.) Spring (Selaginellaceae). Issue 2 (4th March 2018) - Macêdo, Larissa Alves Ribeiro de Oliveira; Oliveira Júnior, Raimundo Gonçalves de; Souza, Grasielly Rocha; de Oliveira, Ana Paula; de Lavor, Érica Martins; Silva, Mariana Gama e; Pacheco, Alessandra Gomes Marques; de Menezes, Irwin Rose Alencar; Coutinho, Henrique Douglas Melo; Pessoa, Cláudia do Ó; da Costa, Marcília Pinheiro; Almeida, Jackson Roberto Guedes da Silva
ABSTRACT: The aim of this study was to evaluate the chemical composition, antioxidant and antibacterial activities and cytotoxicity of fractions from Selaginella convoluta, obtained by liquid–liquid extraction using hexane (Sc-Hex), chloroform (Sc-CHCl3 ) and ethyl acetate (Sc-AcOEt). The phenolic and flavonoid contents were measured by the Folin-Ciocalteu and aluminium chloride methods, respectively. Antioxidant activities were evaluated by using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and β-carotene-linoleic acid bleaching test. The antibacterial effect was evaluated by the method of microdilution and the cytotoxicity analysis in HCT-116 (colon), OVCAR-8 (ovarian) and SF-295 (brain) cells were carried out for MTT (3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2 H -tetrazolium bromide) test. The fractions were positive for the presence of anthracene derivatives, flavonoids, lignans, naphthoquinones, steroids and triterpenoids. The Sc-Hex and Sc-AcOEt showed good antioxidant activities. The fractions of S. convoluta demonstrated antibacterial activity and showed weak cytotoxicity. These activities were correlated with presence of phenolic compounds in active fractions.